Economic freedom and its impact on Foreign Direct Investment: Global overview - Devesh Singh; Zoltán Gál (Review of Economic Perspectives, 2020)
The purpose of this research is to examine the economic freedom (EF) along with its macroeconomic determinants impact on Foreign Direct Investment (FDI) inflow in South Asia, East Asia, Latin America, Middle East, and North Africa, Northern Europe, Southern Europe, Western Europe, Eastern Europe and Sub Saharan Africa. We use Heritage Foundation economic freedom index data over the period of 1999 to 2018 and employ the stepwise multi regression on variables of business freedom, government spending, tax burden, government integrity, property rights, investment freedom, trade freedom and monetary freedom. The results show that EF has a significant positive impact in South Asia, Latin America, East Asia, North Europe and West Europe. However, for the Middle East and North Africa, East European and South European economies EF has an insignificant influence on FDI inflow.
Keywords: F43; F4; P33; 330; Foreign Direct Investments; Economic Freedom; Economic Growth; Macroeconomic Factors